Face to face with your competition[videorecording] : Approaches to group interviews - Cherry, John; Perry, Glenn (VEA, 2007)
If you're looking to enter the workforce, chamces are you'll find yourselves undertaking a group interview sooner rather that later. Companies use the group interview method to assess a number of applications at once, usually using some form of group problem solving exercise. So what are they really looking for in agroup interview? How can you stand out from the crowd?In this essential and informative program, we explore a group interview scenario from both the employer's and applicant's perspective and examine how you can use this interviewing method to your advantage and truly stand up and be noticed.